Artificial Intelligence-Based Public Services in the Digital Era in Indonesia - Didin, Didin; Haedar, Ahmad Wahidiyat; Aliah, Nurul (Universitas Negeri Makassar, 2024)
Technological advancements have driven the transformation of public services in Indonesia. One significant innovation is the implementation of Artificial Intelligence (AI) to enhance the efficiency, effectiveness, and quality of services. This research employs a qualitative approach with a descriptive-analytical method to explore the implementation of Artificial Intelligence (AI) in public services in Indonesia. The findings indicate that AI-based public services offer various benefits, such as automating administrative processes, personalizing services, enabling data-driven decision-making, and improving transparency and accountability. Technologies like chatbots, predictive analytics, and IoT-based systems have been utilized in various sectors, including healthcare, transportation, education, and public safety. However, implementing AI in public services in Indonesia faces challenges, such as digital divides, infrastructure limitations, inadequate regulations, and the need for better digital literacy among both the public and government officials. This study aims to explore the potential and challenges of implementing AI in public services in Indonesia and provide strategic recommendations to maximize the benefits of this technology. With the right approach, AI-based public services are expected to promote inclusivity, enhance public satisfaction, and contribute to achieving sustainable development goals in Indonesia.